Potential angiogenic, immunomodulatory, and antifibrotic effects of mesenchymal stem cell-derived extracellular vesicles in systemic sclerosis - Zhao, Kelin; Kong, Chenfei; Shi, Naixu; Jiang, Jinlan; Li, Ping (Frontiers in Immunology, 2023)
Systemic sclerosis (SSc) is an intricate systemic autoimmune disease with pathological features such as vascular injury, immune dysregulation, and extensive fibrosis of the skin and multiple organs. Treatment options are limited; however, recently, mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have been acknowledged in preclinical and clinical trials as being useful in treating autoimmune diseases and are likely superior to MSCs alone. Recent research has also shown that MSC-EVs can ameliorate SSc and the pathological changes in vasculopathy, immune dysfunction, and fibrosis. This review summarizes the therapeutic effects of MSC-EVs on SSc and the mechanisms that have been discovered to provide a theoretical basis for future studies on the role of MSC-EVs in treating SSc.